The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/0093650210362683
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Causality in Information Acceptance in Narratives: An Example From Science Communication

Abstract: Narratives represent a powerful and ubiquitous form of communication that influence what individuals believe about the world. While the field of narrative persuasion investigates how narratives affect attitudes and behaviors, it rarely considers structural variables discussed in the field of discourse psychology. This study examines the utility of bridging these fields by testing the persuasive influence of novel science information relative to the internal causal structure of a narrative. Results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 63 publications
3
84
0
2
Order By: Relevance
“…Similar stories were used in a number of studies in the field (e.g., Appel & Richter, 2007; Dahlstrom, 2010; 2012; Fazio, Dolan, & Marsh, 2015; Gerrig & Prentice, 1991; Prentice et al, 1997). We deliberately followed this practice as our goal was an independent manipulation of argument strength and narrativity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar stories were used in a number of studies in the field (e.g., Appel & Richter, 2007; Dahlstrom, 2010; 2012; Fazio, Dolan, & Marsh, 2015; Gerrig & Prentice, 1991; Prentice et al, 1997). We deliberately followed this practice as our goal was an independent manipulation of argument strength and narrativity.…”
Section: Discussionmentioning
confidence: 99%
“…In some of these studies the stories as a whole or their main narrative arc suggested a particular stance toward a topic (e.g., a story about a psychiatric patient who murdered a child led recipients to have more negative beliefs about the group of psychiatric patients; Green & Brock, 2000). In other studies, the stories included assertions that were not a key element of the plot (e.g., Appel & Richter, 2007; Dahlstrom, 2010; 2012; Prentice et al, 1997). Prior research indicates that the persuasive influence of narratives can be quite durable, being strong even after two weeks (Appel & Richter, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As such, these facts represent the meaningful unit of content and can be excised from a larger message and inserted into other messages, or even presented alone, with little loss of understanding. In contrast, narrative communication is context-dependent because it derives it meaning from the ongoing cause-and-effect structure of the temporal events of which it is comprised (11)(12)(13). As such, it is much harder to break a narrative into smaller units of meaningful content without either greatly altering the understanding of the smaller unit or rendering the original narrative incoherent (3).…”
Section: Narrativesmentioning
confidence: 99%
“…It is not yet well understood what factors are most important in the development of narratives (13,14). Fiction and nonfiction narratives can engage audiences about equally (22), opening the possibility for creating content without needing to remain true to the details of a particular case study.…”
Section: Prescriptive Scientific Narrativesmentioning
confidence: 99%
“…Within this general structure, narratives may take many different forms, such as fact or fiction, case studies, or dramatic conversations and first-person or third-person perspectives. The relative benefits of these different forms have been examined to some degree (3,4,11), especially as they pertain to a narrative's persuasive power (5,(12)(13)(14), but this paper primarily focuses on the use of narrative to explain science so that a target audience can use concepts to make better decisions in their own lives.…”
mentioning
confidence: 99%